2022
DOI: 10.1002/mrm.29391
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field strength dependent SNR gain at the center of a spherical phantom and up to 11.7T

Abstract: Purpose The SNR at the center of a spherical phantom of known electrical properties was measured in quasi‐identical experimental conditions as a function of magnetic field strength between 3 T and 11.7 T. Methods The SNR was measured at the center of a spherical water saline phantom with a gradient‐recalled echo sequence. Measurements were performed at NeuroSpin at 3, 7, and 11.7 T. The phantom was then shipped to Maastricht University and then to the University of Minnesota for additional data points at 7, 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
4
21
0
Order By: Relevance
“…More quantitative measurements followed. The same (traveling) spherical phantom was scanned at 3 T, 7 T and 11.7 T at NeuroSpin CEA, at 7 T and 9.4 T at the University of Maastricht, and finally at 7 T and 10.5 T at the Center for Magnetic Resonance Research of the University of Minnesota [9]. SNR measurements at the center of the phantom were performed in quasi-identical conditions (phantom, positioning, MR protocol, temperature and volume coil).…”
Section: First Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…More quantitative measurements followed. The same (traveling) spherical phantom was scanned at 3 T, 7 T and 11.7 T at NeuroSpin CEA, at 7 T and 9.4 T at the University of Maastricht, and finally at 7 T and 10.5 T at the Center for Magnetic Resonance Research of the University of Minnesota [9]. SNR measurements at the center of the phantom were performed in quasi-identical conditions (phantom, positioning, MR protocol, temperature and volume coil).…”
Section: First Imagesmentioning
confidence: 99%
“…MRI at ultra-high field (UHF) is a promising technology to explore the human brain at the mesoscopic scale and with unprecedented details enabled by the supra-linear gain in signal-to-noise (SNR) and contrast-to-noise ratio (CNR) with field strength [1][2][3][4][5][6][7][8][9]. The first UHF magnet was an 8 T 800 mm bore system developed by Magnex Scientific Limited for Ohio State University in 1998 [10].…”
Section: Introductionmentioning
confidence: 99%
“…With 7 T human MRI now present in the clinic, there is increasing interest in exploring ever higher magnetic field strengths. This includes pioneering reports on 9.4 T, 10.5 and 11.7 T MRI which lead the way to even higher fields [8][9][10]. This has generated the momentum to drive MR science to take even more ambitious steps into the future, envisioning human MR at 14 T and even 20 T [11][12][13][14][15].…”
Section: Getting Ready To Leave Base Campmentioning
confidence: 99%
“…It has been shown that 7T allows detection of epileptogenic lesions not visible at 3T 23 . Therefore, based on typical acquisitions performed at 3T and 7T, differences in the signal- and contrast-to-noise ratios of T 1 data will impact sensitivity to segment individual nuclei as well as the power to detect patient-control morphometric and T 1 differences at lower field strengths 25,82 .…”
Section: Discussionmentioning
confidence: 99%